The Effect of Kegel Exercise on Pelvic Floor Muscle Endurance in Postpartum Mothers with Spontaneous Birth with Perineal Tears - Ummah , Salma Nurul; Rahmawati, Nurul Aini; Yulianti, Atika (Universitas Muhammadiyah Surakarta, 2024)
Pendahuluan: Kegel exercise merupakan suatu latihan menggunakan metode non invasif dengan cara mengencangkan dan mengendurkan otot dasar panggul, sehingga dapat mempercepat proses penyembuhan perineum untuk meningkatkan daya tahan otot dasar panggul. Metode: Penelitian menggunakan quasy experiment design. Sampel penelitian terdiri dari 20 responden yang dibagi menjadi kelompok perlakuan dan kelompok kontrol. Pada kelompok perlakuan diberikan kegel exercise 2 kali sehari. Penelitian dilakukan selama 14 hari dan diukur menggunakan Modified Oxford Grading Scale. Hasil: Pada uji wilcoxon mendapatkan hasil p= 0,004 (<0,05) maka, terdapat pengaruh pada kelompok perlakuan. Sedangkan pada uji mann whitney mendapatkan hasil p= 0,044 (<0,05) maka, terdapat perbedaan pengaruh pada kedua kelompok. Simpulan: Kegel exercise berpengaruh terhadap peningkatan daya tahan otot dasar panggul pada ibu postpartum kelahiran spontan dengan robekan perineum. Introduction: The Kegel exercise is a non-invasive method that involves the tightening and relaxing of the pelvic floor muscles. This exercise helps to accelerate the healing process of the perineum and enhances the endurance of the pelvic floor muscles. Method: The research employed a quasi-experimental design. The study participants were postpartum mothers who had experienced spontaneous births with perineal tears at Rumah Bidan Rina. Twenty respondents were selected and divided into treatment and control groups. The treatment group received Kegel exercises, while the control group received stretching exercises. The intervention was administered twice a day over a period of 14 days, and the Modified Oxford Grading Scale was used for measurement. Results: The Wilcoxon test indicated a result of p = 0.004 (<0.05), signifying a significant influence on the endurance of the pelvic floor muscles in the treatment group. Moreover, the Mann-Whitney test revealed a result of p = 0.044 (<0.05), highlighting a difference in the effect on pelvic floor muscle endurance between the two groups. Conclusion: The findings suggest that Kegel exercises have a positive influence on increasing pelvic floor muscle endurance in postpartum mothers who have experienced spontaneous births with perineal tears.